Optics of Restorative Justice in the Criminal Justice Legal System in Indonesia - Noor Ihsan, Reza (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
This research discusses the transformation of criminal law enforcement in Indonesia from a retributive justice approach to restorative justice. In the context of a rule of law, judicial institutions, especially the Supreme Court, play an important role in protecting human rights. The emergence of the concept of restorative justice as an alternative for resolving criminal acts emphasizes the reconstruction of the relationship between the perpetrator, victim, and society, as well as restoring the original situation. Data from the Directorate General of Corrections shows overcapacity in correctional institutions, which shows that the retributive approach is no longer adequate. Law Number 11 of 2012 and other regulations have adopted restorative justice in the justice system, with the aim of speeding up resolution, reducing recidivism, and providing space for the participation of all parties in the legal process. This research uses normative juridical methods to analyze restorative justice regulations in various law enforcement institutions, as well as the importance of standardizing their implementation. The study's results reveal that despite the significant recovery potential of restorative justice, its implementation remains unintegrated, thereby impeding legal certainty and the effectiveness of the justice system.